Normalization of heterogeneous computing clusters due to use of virtual nodes - Dudnik, V.A.; Gorban, A.M.; Kudrjavtsev, V.I.; Sereda, T.M.; Us, S.A.; Shestakov, M.V. (Вопросы атомной науки и техники, 2007)
Creation of systems of the distributed computing is the new perspective tendency of development of computing systems. To one of actual problems began maintenance of portable of the software of clustered sites. In this article it is offered to use existing means of a virtualization of the computing environment (system VMWare or similar) for simplification of creation of the software of systems of the distributed calculations. Results of measurement of parameters of a bandwidth and a latency of system of synchronization of a cluster for virtual and real nodes are submitted. Results of the made researches allow recommending use of virtual clusters for simplification of creation of systems of the distributed calculations. Створення систем розподілених обчислень є новою перспективною тенденцією розвитку обчислювальних систем. У зв'язку з цим одним з актуальних завдань стало забезпечення переносу програмного забезпечення кластерних вузлів. Запропоновано використати існуючі засоби віртуализації обчислювального середовища (системи VMWare або аналогічні) для спрощення створення з їхньою допомогою програмного забезпечення систем розподілених обчислень. Представлено результати виміру параметрів смуги пропускання й латентності системи синхронізації кластера для віртуальних і реальних вузлів. Результати виконаних досліджень дозволяють рекомендувати використання віртуальних кластерів для спрощення створення систем розподілених обчислень. Создание систем распределённых вычислений является новой перспективной тенденцией развития вычислительных систем. В связи с этим одной из актуальных задач стало обеспечение переноса программного обеспечения кластерных узлов. Предложено использовать существующие средства виртуализации вычислительной среды (системы VMWare или аналогичные) для упрощения создания с их помощью программного обеспечения систем распределенных вычислений. Представлены результаты измерения параметров полосы пропускания и латентности системы синхронизации кластера для виртуальных и реальных узлов. Результаты произведенных исследований позволяют рекомендовать использование виртуальных кластеров для упрощения создания систем распределённых вычислений.